Luminescence in semi-crystalline zirconium titanate doped with lanthanum - Freitas, G. F. G.; Nasar, R. S.; Cerqueira, M.; Melo, D. M. A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
This paper aims to describe the synthesis of the semi-crystalline and crystalline powder of lanthanum doped with zirconium titanate (65/35), LZT through Pechini method. The analysis done by Raman demonstrated that semi-crystalline phase at 550 degrees C and crystalline phase after 600 degrees C were formed. The XRD pattern shows the ZrTiO4 phase formation demonstrating that La substitutions into the lattice take place. The calcined powder at different temperatures shows a semi-crystalline phase presenting photoluminescence effect when processed at low temperatures. From 300 to 400 degrees C a broadband is observed at 563 nm and 568 nm, respectively. Defects creation such as: Zr3+ center dot Vo(center dot center dot) and Ti3+ - V-O(center dot center dot), Zr and Ti replaced by La with vacancy formation, impurities and imperfections contributed to the photoluminescence effect. However, the main emission is due to a reverse Ti4+ -> O2- or/and Zr4+ -> O2- transition that occur within a regular titanate or zirconate eight-fold coordination [BO8-delta], B = Zr4+, Ti4+. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: photoluminescence; amorphous materials; Pechini method